2022
DOI: 10.3390/buildings12050583
|View full text |Cite
|
Sign up to set email alerts
|

Timber Semirigid Frame Connection with Improved Deformation Capacity and Ductility

Abstract: The present study deals with the innovation and the possibilities of improving the design solution of a frame connection for two selected types of fasteners. All specimens were made of glued laminated timber. Dowel-type mechanical fasteners, a combination of bolts and dowels, and full-threaded screws were used for the connection. The main goal of this research was to replace the typical solution (common dowel-type fasteners) with a more modern, faster, and easier solution in order to improve the load-carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The stress during the collapse reaches the ultimate strength and the maximum plastic deformation reaches the value of 3.68%. On the basis of the experimental testing of used fully threaded screws (see the publication Johanides 2022 [ 43 ]), it can be concluded that the numerical model did not fail due to the rupture of the fasteners. This fact was also verified and confirmed by the experimental testing of those connections.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stress during the collapse reaches the ultimate strength and the maximum plastic deformation reaches the value of 3.68%. On the basis of the experimental testing of used fully threaded screws (see the publication Johanides 2022 [ 43 ]), it can be concluded that the numerical model did not fail due to the rupture of the fasteners. This fact was also verified and confirmed by the experimental testing of those connections.…”
Section: Resultsmentioning
confidence: 99%
“…Four-point bending tests were performed to verify the properties of the used timber. Results of the tests have already been published in Johanides 2022 [ 43 ]. The stands were made of a cross-section of 100/300 mm and the rung was made of a cross-section of 100/300 mm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations